Leadership in Public Health: Opportunities for Young Generations Within Scientific Associations and the Experience of the “Academy of Young Leaders” - Gianfredi, Vincenza; Balzarini, Federica; Gola, Marco; Mangano, Sveva; Carpagnano, Lucia Federica; Colucci, Maria Eugenia; Gentile, Leandro; Piscitelli, Antonio; Quattrone, Filippo; Scuri, Stefania; Mantovani, Lorenzo Giovanni; Auxilia, Francesco; et al. (Frontiers in Public Health, 2019)
This paper outlines the characteristics of scientific leadership and the role of Scientific Associations with their specific activities. The recent activities of the Lombard Academy of Public Health are subsequently described, including the creation, in 2019, of the Academy of young leaders in public health. Comparing to other sectors, scientific leadership dynamics take into consideration different aspects. Besides awards (Nobel Prize or several other) and prestigious affiliations, eventual indicators might be academic roles, fundraising abilities, relevant positions among scientific associations, editors of prestigious journals or editorial series and, more recently, high bibliometric indicators. The peculiar topics of public health encompass interactions with institutions, authorities, politicians, involved in different levels in health policies. Recently, in Italy, the Ministry of Health has identified parameters to be accreditated as a scientific and technical association. The role of SItI (Italian Society of Hygiene), EUPHA, ASPHER, and WFPHA appears relevant in PH, in national and international contexts, with Italian praiseworthy members constantly achieving leading roles. Considering that few training opportunities aimed to improve research and leadership skills are available, Accademia Lombarda di Sanità Pubblica (ALSP) designed the AYLPH (Academy of Young Leaders in Public Health) program. AYLPH program is a 1-year training to shape leadership skills among young professionals. A set of didactic, theoretical and practical methods was offered and evaluated.